2021
DOI: 10.1002/vetr.74
|View full text |Cite
|
Sign up to set email alerts
|

Owner quality of life, caregiver burden and anticipatory grief: How they differ, why it matters

Abstract: Background: Understanding client perspective is important for veterinary communications, particularly during problem visits. Key client experiences of caregiver burden, anticipatory grief and quality of life (QoL) have been previously examined in this context, but never simultaneously considered. Methods: A sample of 393 owners of an elderly or seriously ill companion animal was recruited online to complete cross‐sectional measures of psychosocial function, companion animal presentation and demographics. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…When individuals worry about something negative that might happen in future, it can further increase their anxiety in the present ( Schubert et al, 2020 ), and we found that owners often worried about what might happen to their dog or what would happen to the dog if they die first. They also suffered anticipatory grief ( Spitznagel et al, 2021 ) about how they would cope with the loss of their dog. Even though the caregiving responsibilities are stressful, it is interesting to note that caregiving for a severely ill animal has been suggested to create less burden and more positive attitude compared to caregiving for a human family member ( Karysa et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…When individuals worry about something negative that might happen in future, it can further increase their anxiety in the present ( Schubert et al, 2020 ), and we found that owners often worried about what might happen to their dog or what would happen to the dog if they die first. They also suffered anticipatory grief ( Spitznagel et al, 2021 ) about how they would cope with the loss of their dog. Even though the caregiving responsibilities are stressful, it is interesting to note that caregiving for a severely ill animal has been suggested to create less burden and more positive attitude compared to caregiving for a human family member ( Karysa et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Spitznagel and colleagues' study 15 confirm that vet-client communication can greatly influence how owners cope with managing their sick or elderly companion animals. 16 Furthermore, as recent research has identified a clear link between client distress and stress and burnout in vets, 17 effective vet-client communication can also have a positive impact on vets' wellbeing.…”
Section: What You Need To Knowmentioning
confidence: 67%
“…Therefore, the study by Spitznagel and colleagues, summarised on p 352 of this issue of Vet Record, represents a real breakthrough in this field. 15 This study found that the constructs of anticipatory grief, caregiver burden and quality of life are not interchangeable in owners of elderly or seriously ill companion animals and may differentially influence owners' decisions and behaviour.…”
Section: What You Need To Knowmentioning
confidence: 80%
See 1 more Smart Citation
“…The emotional burden that euthanasia represents for the clinician and the guardian is another critical topic that needs to be broadly taught in veterinary medicine. While it might not be the direct role of veterinarians to treat this problem, studies by Spitznagel et al [ 93 ] have shown that distress in clients can impact their perspective towards euthanasia and they can hastily decide before considering previous treatments for their pet. The way the owner perceives animal welfare and their level of empathy is also an interesting research field where high levels of empathy have been associated with euthanasia decisions at later stages of the disease [ 94 ], and emotional support provided by veterinarians is proposed as a compassionate way to conduct euthanasia [ 95 ].…”
Section: Perspectivesmentioning
confidence: 99%